Death of the Soldier and Immortality of War in Frank Ormsby’s A "Northern Spring" - Marzec, Karolina (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The paper analyzes the collection of the Northern Irish poet Frank Ormsby entitled A Northern Spring published in 1986. On the basis of selected poems, the author of this paper aims to examine the poet’s reflections about World War II, the lives of the soldiers, and the things that remain after a military combat, which are both physical and illusive. The poems included in the volume present the author’s reflections upon the senselessness of war and dying, short lives of the soldiers, the awareness of their own meaninglessness in comparison to the broader picture, and the contradictory and desperate need to be remembered nevertheless. They also show what is left of the soldiers and the war, as well as how life goes on, with or without them.